(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
Information and Communication Technology (ICT) has become a pivotal aspect of modern education. However, it has offered opportunities and posed challenges in education. This study explores university-level English teachers’ (ULETs’) experiences, opportunities, challenges, and aspirations in integrating ICT into education. Using an interpretative paradigm, qualitative approach, and phenomenological design, data were collected through semi-structured interviews and reflection notes from ten English teachers across five campuses of Tribhuvan and Mid-West universities. The findings revealed that ICT significantly contributed to student motivation and empowerment, facilitated autonomous exploration of learning materials, fostered peer and mentor support, enabled asynchronous and synchronous collaboration, and enhanced teacher professional development (TPD). The study also identified challenges, including frequent power outages, inadequate resources and skills, and infrastructure maintenance and use issues. The study suggests that stakeholders prioritize enforcing better ICT policies in education, allocate sufficient budgets for infrastructure development, and provide extensive teacher training. Regular monitoring and follow-up are essential to ensure the effective use of ICT in education. Additionally, further research is recommended to explore the experiences of students and other educational stakeholders at various levels.